Ginsenoside Rg3 Prolongs Survival of the Orthotopic Hepatocellular Carcinoma Model by Inducing Apoptosis and Inhibiting Angiogenesis - Shen Hu; Yan Zhu; Xiangyang Xia; Xiaobo Xu; Fen Chen; Xudong Miao; Xinmei Chen (Analytical Cellular Pathology)
Aim. Microvessel density is a marker of tumor angiogenesis activity for development and metastasis. Our preliminary study showed that ginsenoside Rg3 (Rg3) induces apoptosis in hepatocellular carcinoma (HCC) in vitro. The aim of this study was to investigate the cross-link for apoptosis induction and antiangiogenesis effect of Rg3 on orthotopic HCC in vivo. Methods. The murine HCC cells Hep1-6 were implanted in the liver of mouse. With oral feeding of Rg3 (10 mg/kg once a day for 30 days), the quantitative analysis of apoptosis was performed by using pathology and a transmission electron microscope and microvessel density was quantitatively measured by immunohistochemical staining of the CD105 antibody. The mice treated with Rg3 (n=10) were compared with the control (n=10) using Kaplan-Meier analysis. Animal weight and tumor weight were measured to determine the toxicity of Rg3 and antitumor effect on an orthotopic HCC tumor model. Results. With oral feeding of Rg3 daily in the first 30 days on tumor implantation, Rg3 significantly decreased the orthotopic tumor growth and increased the survival of animals (P<0.05). Rg3-treated mice showed a longer survival than the control (P<0.05). Rg3 treatment induced apoptosis and inhibited angiogenesis. They contributed to the tumor shrinkage. Rg3 initialized the tumor apoptotic progress, which then weakened the tumor volume and its capability to produce the vascularized network for further growth of the tumor and remote metastasis. Conclusion. Rg3 inhibited the activation of microtumor vessel formation in vivo besides its apoptosis induction. Rg3 may be used as an adjuvant agent in the clinical HCC treatment regimen.